Population viability and harvest sustainability for Madagascar lemurs. Issue 1 (10th September 2018) - Brook, Cara E.; Herrera, James P.; Borgerson, Cortni; Fuller, Emma C.; Andriamahazoarivosoa, Pascal; Rasolofoniaina, B. J. Rodolph; Randrianasolo, J. L. Rado Ravoavy; Rakotondrafarasata, Z. R. Eli; Randriamady, Hervet J.; Dobson, Andrew P.; Golden, Christopher D.
Abstract: Subsistence hunting presents a conservation challenge by which biodiversity preservation must be balanced with safeguarding of human livelihoods. Globally, subsistence hunting threatens primate populations, including Madagascar's endemic lemurs. We used population viability analysis to assess the sustainability of lemur hunting in Makira Natural Park, Madagascar. We identified trends in seasonal hunting of 11 Makira lemur species from household interview data, estimated local lemur densities in populations adjacent to focal villages via transect surveys, and quantified extinction vulnerability for these populations based on species‐specific demographic parameters and empirically derived hunting rates. We compared stage‐based Lefkovitch with periodic Leslie matrices to evaluate the impact of regional dispersal on persistence trajectories and explored the consequences of perturbations to the timing of peak hunting relative to the lemur birth pulse, under assumptions of density‐dependent reproductive compensation. Lemur hunting peaked during the fruit‐abundant wet season (March–June). Estimated local lemur densities were roughly inverse to body size across our study area. Life‐history modeling indicated that hunting most severely threatened the species with the largest bodies (i.e., Hapalemur occidentalis, Avahi laniger, Daubentonia madagascariensis, and Indri indi), characterized by late‐age reproductive onsets and long interbirth intervals. In model simulations, lemur dispersal within a regional metapopulation buffered extinction threats when a majority of local sites supported growth rates above the replacement level but drove regional extirpations when most local sites were overharvested. Hunt simulations were most detrimental when timed to overlap lemur births (a reality for D. madagascariensis and I. indri). In sum, Makira lemurs were overharvested. Regional extirpations, which may contribute to broad‐scale extinctions, will be likely if current hunting rates persist. Cessation of anthropogenic lemur harvest is a conservation priority, and development programs are needed to help communities switch from wildlife consumption to domestic protein alternatives. Abstract : Article impact statement : Lemur hunting will yield regional extirpations if continued unabated; domestic proteins are needed to mitigate human reliance on wild food. Abstract : Viabilidad Poblacional y Sustentabilidad de Explotación de los Lémures de Madagascar Resumen: La caza de subsistencia representa un reto de conservación ante el cual la preservación de la biodiversidad debe balancearse con la salvaguardia del sustento humano. A nivel mundial, la caza de subsistencia amenaza a las poblaciones de primates, incluyendo a los lémures endémicos de Madagascar. Usamos análisis de viabilidad poblacional (PVA, en inglés) para evaluar la sustentabilidad de la caza de lémures en el Parque Natural Makira, Madagascar. Identificamos tendencias en la caza estacional de 11 especies de lémur en Makira a partir de información obtenida con entrevistas a hogares, estimamos las densidades locales de lémures en las poblaciones adyacentes a aldeas focales por medio de censos de transecto, y cuantificamos la vulnerabilidad a la extinción para estas poblaciones con base en parámetros demográficos específicos por especie y las tasas de caza derivadas empíricamente. Comparamos el modelo Lefkovitch basado en estadios con matrices periódicas de Leslie para evaluar el impacto de la dispersión regional sobre las trayectorias de persistencia y exploramos las consecuencias de las perturbaciones al momento justo del punto máximo de caza en relación con el pulso de nacimiento de lémures, bajo suposición de la compensación reproductiva dependiente de la densidad. La caza de lémures alcanzó su punto máximo durante la temporada lluviosa con abundancia de frutos (marzo – junio). Las densidades locales estimadas de lémures fueron aproximadamente inversas al tamaño corporal a lo largo de nuestra área de estudio. El modelado de historias de vida indicó que la caza amenazó con mayor severidad a las especies con tallas mayores (es decir, Hapalemur occidentalis, Avahi laniger, Daubentonia madagascariensis, Indri indri), caracterizadas por tener un arranque reproductivo a una edad tardía e intervalos largos entre nacimientos. En las simulaciones modeladas, la dispersión de los lémures dentro de una metapoblación regional amortiguó las amenazas de extinción cuando una mayoría de sitios locales respaldó las tasas de crecimiento por encima del nivel de reemplazo pero condujo a las extirpaciones locales cuando la mayoría de los sitios tuvo sobreexplotación. Las simulaciones de caza fueron más nocivas cuando se programaron para sobreponerse a los nacimientos de lémures x(una realidad para D. madagascariensis e I. indri). En resumen, existe una sobreexplotación de lémures en Makira. Las extirpaciones regionales, las cuales pueden contribuir a las extinciones a escala general, serán probables sí las tasas de caza actuales continúan. El cese de explotación humana de lémures es una prioridad para la conservación, y se necesitan programas de desarrollo para ayudar a las comunidades a cambiar el consumo de fauna silvestre por alternativas domésticas de proteína. 摘要: 生计狩猎是保护工作的一项挑战, 它要求保护生物多样性必须与保障人类生计相平衡。全球的灵长类动物, 包括马达加斯加特有的狐猴, 都面临着生计狩猎的威胁。我们用种群生存力分析评估了马达加斯加 Makira 自然公园狐猴狩猎的可持续性。利用访问调查的数据, 我们确定了Makira自然公园 11 种狐猴面临的季节性狩猎态势, 并通过样带调查估计了村庄附近狐猴的局域种群密度, 还根据物种特异的种群参数和狩猎率经验值量化了这些种群灭绝的脆弱性。我们比较了基于阶段的 Lefkovitch 矩阵与周期性的 Leslie 矩阵, 以评估区域性扩散对种群续存的影响, 还在密度依赖性繁殖补偿的假设下探讨了狩猎高峰期相对于狐猴出生潮发生扰动所带来的影响。水果丰富的雨季 (三月到六月) 是狩猎狐猴的高峰期。在我们的研究区域, 区域狐猴密度的估计值大致与体型大小成反比。生活史建模表明, 体型最大的物种 (如 Hapalemur occidentalis, Avahi laniger, Daubentonia madagascariensis 和 Indri indi ) 受狩猎威胁最为严重, 这些物种多具有开始繁殖的年龄晚、繁殖间隔长的特点。在模型模拟中, 当大多数局部位点的种群增长率高于更替水平时, 区域集合种群中狐猴的扩散可以缓冲灭绝的威胁, 而当大多数位点都受到过度狩猎时, 扩散则会导致区域性灭绝。当狩猎与狐猴出生时间重合时, 模拟得出狩猎的危害最大 ( D. madagascariensis 和 I. indri 的真实情况如此) 。总的来说, Makira自然公园的狐猴已受到过度狩猎。如果维持现有的狩猎率, 狐猴可能会发生区域性灭绝, 进而导致大范围的灭绝。目前的保护重点是停止人类对狐猴的狩猎行为, 需要推动发展计划来帮助当地社区居民从野生动物转向以家畜作为肉类食物来源。【翻译: 胡怡思; 审校: 聂永刚】